Sarcopenia: prevalence and its main risk factors in older women - Bogucka, Aleksandra; Kopiczko, Anna; Charzewska, Jadwiga (Anthropological Review, 2023)
Introduction: Sarcopenia is a major public health concern. It is defined as a progressive and generalized skeletal muscle disorder that is associated with an increased likelihood of falls, fractures, physical disability, and ultimately, premature death. Objective: The aim of the study was to assess the prevalence and determine the role of physical activity, nutrient intake, and selected risk factors for the development of sarcopenia in older women. Methods: The study involved 302 women aged ≥65 years (mean age: 72.1± 5.9 years). Bioelectrical impedance analysis of body composition, static muscle strength measurements, Timed Up and Go test, and the assessment of current physical activity using accelerometers were performed. Diets were assessed using the 24-h recall method from two non-consecutive days. The energy and nutrient content of diets was calculated using the computer program DIETA 6. Results: Sarcopenia was present in 28.8% of the women studied. The most important factor in the decrease in the risk of sarcopenia was protein intake ≥ 0.9 g/kg b.m. (OR=0.08;p<0.001), and physical activity ≥ 4000 steps/day. However, these results were not statistically significant (OR=0.58; p=0.08). Furthermore, the risk of developing sarcopenia increased as BMI (OR=1.36; p<0.001) or percent of body fat (OR=1.29; p<0.001) increased.